The last Martin - Friesen, Jonathan (Grand Rapids, Mich. : Zonderkidz, 2011)
Thirteen-year-old Martin Boyle struggles to break a family curse after discovering that he has only twelve weeks to live.
School Library Journal starred
Wilson's Children
Wilson's Junior High School
Kirkus Starred, March 2011
School Library Journal starred, May 2011
Wilson's Children, September 2011
Keywords: Blessing and cursing -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Emotional problems of children -- Juvenile fiction; Blessing and cursing -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction; Blessing and cursing -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction